Development of broad‐spectrum human monoclonal antibodies for rabies post‐exposure prophylaxis - Paola De Benedictis; Andrea Minola; Elena Rota Nodari; Roberta Aiello; Barbara Zecchin; Angela Salomoni; Mathilde Foglierini; Gloria Agatic; Fabrizia Vanzetta; Rachel Lavenir; Anthony Lepelletier; Emma Bentley; et al. (EMBO Molecular Medicine)
Abstract Currently available rabies post‐exposure prophylaxis (PEP) for use in humans includes equine or human rabies immunoglobulins (RIG). The replacement of RIG with an equally or more potent and safer product is strongly encouraged due to the high costs and limited availability of existing RIG. In this study, we identified two broadly neutralizing human monoclonal antibodies that represent a valid and affordable alternative to RIG in rabies PEP. Memory B cells from four selected vaccinated donors were immortalized and monoclonal antibodies were tested for neutralizing activity and epitope specificity. Two antibodies, identified as RVC20 and RVC58 (binding to antigenic site I and III, respectively), were selected for their potency and broad‐spectrum reactivity. In vitro, RVC20 and RVC58 were able to neutralize all 35 rabies virus (RABV) and 25 non‐RABV lyssaviruses. They showed higher potency and breath compared to antibodies under clinical development (namely CR57, CR4098, and RAB1) and commercially available human RIG. In vivo, the RVC20–RVC58 cocktail protected Syrian hamsters from a lethal RABV challenge and did not affect the endogenous hamster post‐vaccination antibody response.